A risk based approach for the assessment of natural hazards in the UAE - Alsenaani, Haitham (International Journal of Scientific World, 2013)
Civil developments have raised the necessity for conducting natural hazards risk assessment. This study employs the method of risk matrix applied on natural hazards for seismic, flooding and tsunami. In addition to the former hazards, Dust-Sand Storms “DSS” and climate change have been assessed in a form of context discussion. DSS assessment in particular is a vital element in terms of evaluating the natural hazards. This issue is unique and site specific for the UAE. The screening of a variety of information from different advanced countries identified that they do not consider DSS within their risk assessments. This study has been conducted using mainly the risk matrix as the primary assessment tool combining the probability of occurrences and severity.Several risk matrices are developed to accumulate all historical, scientific and other global data that is used for the comparison of risk levels between the UAE and the rest of the world. In this work, the susceptibility of regions to natural hazards has been taken into account under the aspects of historical events recorded with respect to the geographical location. Vulnerable regions are represented through hazard maps as a result of the risk assessment. The overall outputs show encouraging results in some regions of the UAE. Although the assessment presents lower risk regions, it should be emphasized that minimizing the uncertainty by acquiring more historical data is required.